Implementasi Strategi Digital Branding Berbasis Hyperlocal SEO untuk Perluasan Jangkauan Konsumen UKM Kopi Jepara - Riansyah, Andi; Syakhroni, Akhmad; Sagaf, Muhammad; Damaivila, Iven Aurananta (Abdimas Universal, 2026)
Small and Medium Enterprises (SMEs) in the coffee sector in Jepara Regency have great potential to support local economic growth and the development of the region's tourism sector. However, most coffee SMEs still face challenges in digital marketing, particularly with location-based searches, which are increasingly used by consumers. The low visibility of coffee SMEs on Google Maps makes it difficult for both local consumers and tourists to find business locations online. This community service activity aims to implement a hyperlocal SEO-based digital branding strategy through the utilization of Google Maps with the Google Business Profile feature. The service method is carried out through mentoring for coffee SMEs, including creating and verifying business profiles, optimizing business information using local keywords, managing customer reviews, and integrating Google Maps profiles with social media and SME websites. The results of the activity show an increase in the visibility of coffee SMEs in local search results, an increase in consumer interactions in the form of route searches and phone calls, and an increase in direct visits to business locations. The implementation of this strategy has proven effective as a low-cost, easy-to-implement, and sustainable digital branding solution for expanding local consumer reach.